Hermetismo en sociedades de Camponotus morosus Smith, 1858 (Hymenoptera, Formicidae) en nidos artificiales - Ipinza Regla, J.H.=700 1 Lucero, A.; Morales, M.A.
(En, Es)
Ilus., 21 ref
Keywords: INSECTA; HYMENOPTERA; FORMICIDAE; INTEGRACION; OLOR; CHILE; HORMIGAS; COMPONOTUS MOROSUS; HERMETISMO; NIDOS ARTIFICIALES; REVISTA CHILENA DE ENTOMOLOGIA